Analysis of soccer goalkeeper performance and shot scenarios in the 2022 World Cup - Numazu, N.; Hirashima, Y.; Matsukura, K. (Journal of Physical Education and Sport, 2024)
Problem Statement: In soccer, teams seldom achieve victory by scoring multiple goals, therefore, preventing goals is crucial for winning matches. The goalkeeper plays a pivotal role in this aspect by blocking shots from opposing players considerably impacting the game`s outcome. However, the connection between the characteristics of shot situations and the movements of goalkeepers is not well understood. Purpose: This study aimed to enhance goalkeeper training strategies by analyzing the relationship between shot situations and goalkeeper movements during the 2022 FIFA World Cup in Qatar. Approach: The research categorized 432 on target shots from all 64 matches based on factors such as location, outcome, body part used, and the events leading up to each shot. Goalkeeper actions were classified into diving after preparatory motion, stepping and diving after preparatory motion, and blocking. Results: Areas near the center of the goal are dangerous for goalkeepers, with a higher frequency of goals than expected. This study found that goalkeepers commonly used diving after preparatory motion, highlighting its importance across all areas. However, blocking occurred more frequently in high-pressure areas where time and spatial constraints are more significant, suggesting the need to prioritize this technique to reduce shooting angles and increase shot-stopping success. In contrast, a higher incidence of catching, stepping, and diving after preparatory motion was observed in areas farther from the goal where goalkeepers had more time to react. These areas also had more controlled shots, often involving two or more touches. Conclusions: This study suggests that goalkeeper training should be tailored to different shot locations, focusing on quick, reactive movements, such as blocking dangerous areas and positioning, and controlled dives in less pressurized areas. This study provides a framework for designing goalkeeper training sessions that reflect actual match conditions, emphasizing the need for scenario-based practices. Future research could refine these strategies by considering additional factors, such as the specific foot used for shooting and the exact placement of the shot on the goal.